Inspiration Core Characteristics, Component Processes, Antecedents, and Function. (article). - Thrash, Todd M.
The authors examined the core characteristics, component processes, antecedents, and function of state inspirations. In studies 1 and 2, inspiration was contrasted with baseline experience and activated positive affect (PA) using a vivid recall methodology. Results supported the tripartite conceptualization of inspiration. Confirmatory factor analysis indicated that inspiration may be decomposed into separate processes related to being inspired "by" and being inspired "to." Study 3 found that daily inspiration is triggered by illumination among individuals high in receptive engagement, whereas activated PA is triggered by reward salience among individuals high in approach temperament. Approach temperament was also implicated in being inspired "to." Inspiration and activated PA appear to serve different functions: Transmission, acquisition respectively. -- (from the author)
Keywords: Psychology-Periodicals.